Violation and the emancipatory subject: restorative justice and a tale of two absences. - Wilson, Amanda (Journal of Critical Realism, 2025)
In this paper I explore the philosophical grounds of critiques of restorative justice and their ethical limits by addressing two absences. George Pavlich's critical theory of restorative justice qua the 'imitor paradox' provides a unifying critical account that helpfully illuminates the ways in which restorative justice has failed to give effect to its radical promise of emancipation from violation. However, I find that its poststructural/postmodern grounding means that the critique is unable to transcend itself. This is the first tale of absence I identify. The second emerges from its critical realist development. In absenting the absence of the 'imitor paradox', I draw on Roy Bhaskar's concrete universal/singular ethics, but find a further absence there in that it does not articulate the necessary ontological (moral, psychological, social) grounds for restorative justice ethics. A constellational development of the concrete universal/singular grounds the radical value of restorative justice beyond the imitor paradox.